Effects of walking trainings on walking function among stroke survivors: a systematic review. Issue 1 (March 2018) - Ilunga Tshiswaka, Daudet; Bennett, Crystal; Franklin, Cheyanne
Abstract : Physical function is often compromised as a result of stroke event. Although interventions propose different strategies that seek to improve stroke survivors' physical function, a need remains to evaluate walking training studies aimed at improving such physical function. The aim of this review was to assess the available literature that highlights the impact of walking training on enhancing walking for stroke survivors. We performed a systematic literature review of online databases – Google Scholar, PubMed, CINHAL, Cochrane Library, Scopus, and EBSCO – with the following inclusion criteria: manuscript published from 2005 to 2016, written in English, with treatment and control groups, for walking training studies aimed at improving physical function among stroke survivors. Findings indicated that walking speed, walking distance, and gait speed were the most used outcome variables for measuring improved physical function among stroke survivors. Importantly, proposed interventions involved either overground or treadmill walking trainings, if not both. Preserved locomotor improvements were not noted in all interventions at follow-up. Some interventions that used walking treadmill training augmented by auditory stimulations reported significant improvements in physical function compared with overground walking training augmented by auditory stimulations. The imperative to improve physical function among stroke survivors with physical impairment is paramount, as it allows survivors to be socially, emotionally, and physically more independent. In general, we note an insufficiency of research on the interaction between physical function and socialization among stroke survivors.